2012
DOI: 10.1002/jwmg.337
|View full text |Cite
|
Sign up to set email alerts
|

Interseasonal movements of greater sage‐grouse, migratory behavior, and an assessment of the core regions concept in Wyoming

Abstract: Animals can require different habitat types throughout their annual cycles. When considering habitat prioritization, we need to explicitly consider habitat requirements throughout the annual cycle, particularly for species of conservation concern. Understanding annual habitat requirements begins with quantifying how far individuals move across landscapes between key life stages to access required habitats. We quantified individual interseasonal movements for greater sage-grouse (Centrocercus urophasianus; here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
115
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(126 citation statements)
references
References 35 publications
10
115
1
Order By: Relevance
“…Teton, Wyoming, Wind River, and Gros Ventre ranges; Figures 1 and 2) that most likely limit Greater Sage-Grouse dispersal (Hupp and Braun 1991, Musil et al 1993, Reese and Connelly 1997, Garton et al 2011). Due to these high elevation and large forested tract barriers, the most likely dispersal route from Jackson Hole goes to the east and south toward the Pinedale population ( Figure 2); however, the Euclidian distance between the 2 populations exceeded the interseasonal movement and dispersal of Greater SageGrouse reported in Wyoming (Holloran and Anderson 2004, Bedrosian et al 2010, Fedy et al 2012) further supporting the differentiation we found with population genetics.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Teton, Wyoming, Wind River, and Gros Ventre ranges; Figures 1 and 2) that most likely limit Greater Sage-Grouse dispersal (Hupp and Braun 1991, Musil et al 1993, Reese and Connelly 1997, Garton et al 2011). Due to these high elevation and large forested tract barriers, the most likely dispersal route from Jackson Hole goes to the east and south toward the Pinedale population ( Figure 2); however, the Euclidian distance between the 2 populations exceeded the interseasonal movement and dispersal of Greater SageGrouse reported in Wyoming (Holloran and Anderson 2004, Bedrosian et al 2010, Fedy et al 2012) further supporting the differentiation we found with population genetics.…”
Section: Discussionsupporting
confidence: 77%
“…This study identified the Greater Sage-Grouse populations in Jackson Hole and Gros Ventre as genetically isolated with reduced neutral genetic diversity compared to nearby populations in Wyoming and southeast Montana. We were unable to obtain tissue samples from Greater Sage-Grouse populations in Idaho; however, the distance between populations in Jackson Hole and eastern Idaho are beyond the dispersal distance documented for Greater Sage-Grouse based on radiotelemetry (Fedy et al 2012), and the Teton Range eastern slope rises sharply from its base to~2 km above Jackson Hole (Figure 1). Future studies should include eastern Idaho to investigate whether connectivity exists between the 2 areas.…”
Section: Conservation Implications and Future Considerationsmentioning
confidence: 97%
“…The algorithm iteratively joined each sampling location based on distance using the Lance–Williams dissimilarity formula (Legendre & Legendre, 2012). Subsequently, we used a cut distance to differentiate clusters separated by a distance >25 km, which represented the maximum average summer to winter movement distance for any population in Wyoming (Fedy et al., 2012). We used a minimum sample size of eight individuals per genetic cluster for all subsequent analyses.…”
Section: Methodsmentioning
confidence: 99%
“…One way of modeling the biological importance of multiple landscape features is through the use of habitat indices. Habitat indices are typically derived from occurrence or radiotelemetry data and are used to predict the probability of occupancy across a landscape based on the suitability of habitat (Fedy et al., 2012; Phillips, Anderson, & Schapire, 2006) or the probability of selection for habitat types (Gubili et al., 2017; Shafer et al., 2012). Using habitat indices in landscape genetic models can assist with establishing a direct link between model results and management actions, and can alleviate some of the issues related to testing a multitude of landscape variables (i.e., type I error).…”
Section: Introductionmentioning
confidence: 99%
“…Sage-grouse fidelity to leks and the conspicuous behavior of males make it possible to estimate population trends. In an attempt to compare trends among populations, recent lek monitoring protocols have been published (Connelly et al 2003;Connelly and Schroeder 2007;Fedy et al 2012). During a lek count, attending males are directly counted from a distance to prevent disturbance of breeding behavior but still maintain high visibility and count accuracy (Patterson 1952;Jenni and Hartzler 1978;Connelly et al 2003).…”
Section: Introductionmentioning
confidence: 99%